Follow-up assessment of pulmonary functions in mechanically ventilated children after discharge from pediatric intensive care unit: A developing country perspective - Garg, Meenal; Bhargava, Siddharth; Pooni, Puneet A; Das, Rashmi Ranjan; Mishra, Nihar Ranjan (Indian Journal of Child Health, 2017)
Background: There is a paucity of data on the pulmonary function tests (PFTs) in pediatric mechanically ventilated patients, especially in a developing country setting. Materials and Methods: This prospective study was carried out in the pediatric intensive care unit over 15 months. The PFTs were measured using spirometry at discharge, at 3 and 6 months. Results: Of 32 eligible children, 20 (mean age 9 ± 2.62 years) completed the 6-month follow-up. The most common indications for mechanical ventilation were respiratory (45%) and neurological (35%) causes. At the end of 6 months, 65% children had abnormal lung function (restrictive pattern). Patients with longer duration of ventilation, high peak pressures, and high fractional inhaled oxygen had a trend toward more abnormality in the lung function. Conclusions: Pediatric mechanically ventilated patients developed restrictive pulmonary defects after discharge that gradually improved over time. The majority was asymptomatic and reported no lifestyle limitations. There is a need for longer follow-up studies to assess the lung function and clinical condition postdischarge.